Treatment discontinuation of remotely delivered cognitive remediation for schizophrenia: a systematic review and meta-analysis - Wen, Min; Zhang, Jie; Jiang, Keqing; Liu, Juan; Zhu, Xiaodan (Frontiers in Psychiatry, 2025)
IntroductionCognitive remediation therapy (CRT) is a pivotal treatment for cognitive impairments in patients with schizophrenia. However, there is a large proportion of community-dwelling patients with schizophrenia, and access to this therapy is not fully equalized across regions. The introduction of remotely delivered CRT presents a promising solution to these limitations. Given the substantial variation in settings for remotely delivered CRT, its treatment discontinuation and the factors influencing it remain to be fully elucidated. This meta-analysis aims to examine the treatment discontinuation of remotely delivered CRT and the factors influencing its treatment discontinuation.MethodsThis study systematically searched PubMed, Embase, EBSCO, WHO ICTRP, ClinicalTrials, ProQuest, and BASE databases to identify randomized controlled trials involving remotely delivered CRT. Meta-analyses were performed using both random-effects and fixed-effects models. Subgroup and meta-regression analyses were employed to investigate potential factors affecting the treatment discontinuation of remotely delivered CRT.ResultThe literature search yielded 2173 studies. 20 studies met the inclusion criteria and reported on 20 randomized controlled trials comparing remotely delivered CRT with control groups. Dropout rates were 22.96% for the remotely delivered CRT group and 20.82% for the control group. Meta-analysis results indicated no significant difference in dropout rate between the two groups (OR 0.99 [95% CI 0.78-1.25], p=0.901). Subgroup and meta-regression analyses identified that the development of cognitive strategies, facilitating the transfer of cognitive gains to everyday functioning, and the inclusion of all core CRT components were associated with lower rates of treatment discontinuation in remotely delivered CRT.ConclusionRemotely delivered CRT demonstrates efficacy comparable to other forms of cognitive remediation, yet it exhibits a higher rate of treatment discontinuation. Future studies should consider the specificities of the target population and their environmental context, designing more meticulous and rigorous protocols to optimize the efficacy and treatment continuation of remotely delivered CRT.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42024610531.